A precise measurement of the B 0 meson oscillation frequency - Aaij, Roel; Abellán Beteta, C.; Adeva, B.; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Gerick, David; Gersabeck, Evelina; et al. (The European physical journal. C, Particles and fields, 2016)
The oscillation frequency, Δmd, of B0 mesons is measured using semileptonic decays with a D− or D∗− meson in the final state. The data sample corresponds to 3.0fb−1 of pp collisions, collected by the LHCb experiment at centre-of-mass energies s√ = 7 and 8TeV. A combination of the two decay modes gives Δmd=(505.0±2.1±1.0)ns−1, where the first uncertainty is statistical and the second is systematic. This is the most precise single measurement of this parameter. It is consistent with the current world average and has similar precision.